Optimalisasi Peran Mahasiswa dalam Pengajaran Al-Qur'an Berbasis Metode Qiro'ati di TPQ MI Roudlotul Islamiyah Wonoayu Sidoarjo - Rifda Arifa Sani (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to optimize the role of students in teaching the Qur'an based on the Qiro'ati method at TPQ MI Roudlotul Islamiyah, Wonoayu, Sidoarjo, through the Asset-Based Community Development (ABCD) approach. The activity was conducted on February 14, 2026, involving direct participation of students from Universitas Sunan Giri Surabaya as teaching assistants. To address the declining enthusiasm observed among students, several interactive strategies were introduced, including question-and-answer evaluations, icebreakers, and reward-based quizzes, without altering the established Qiro'ati learning system. These strategies proved effective in reviving students' interest and active participation during lessons. In addition, the routine practice of tadarrus Al-Qur'an before class and the Majelis Mu'allimil Qur'an (MMQ) program served as key mechanisms for maintaining teachers' recitation quality and pedagogical competence. The findings suggest that combining the Qiro'ati method with varied interactive techniques can significantly enhance the learning atmosphere and student engagement in Qur'anic education at the elementary level.